RESEARCH ON SUBLINICAL MASTITIS EFFECT ON MILK QUALITY - C. ŞONEA; D. COLCERI; V. BĂCILĂ (Scientific Papers Animal Science and Biotechnologies, 2023)
Having considered that mastitis are the most costly disease in dairy farms, the present study was conducted in order to emphasize the effect of subclinical mastitis on milk composition and hygiene. On this purpose, large amounts of statistical data were analyzed, including all three main bovine breeds in Romania. Firstly, mastitis causing factors have been studied (breed, age, season, milking system. Afterwards, comparative study was achieved on fat, protein, lactose, salts). A significant increase in salts concomitantly with decreasing lactose percent has been revealed. Pathogen involved in subclinical mastitis has been also analyzed. According to our research, defectuous mechanical milking is the most frequent cause of subclinical mastitis occurrence.